Wars, Laws, Rights and the Making of Global Insecurities - Rogers, Damien. author. aut Link
VIII, 115 p. 1 illus.
Keywords: This book offers a unique and timely political analysis of war, international law and human rights, and the important interconnections among them. It questions why war features as a foundational problem in contemporary world affairs and explores how international law is used to manage this and other types of political violence. Challenging conventional thinking that understands war as a problem to be solved and law as an antidote to organized but unruly violence, this book situates the promotion and protection of human rights within the wider context of the modernist project, particularly during the epoch of the Anthropocene. Taking a critical perspective that draws on concepts found in the work of Michel Foucault, Pierre Bourdieu and Bruno Latour, this book casts new light on the ways in which the politics of war, law and rights produces profound insecurities for the human species as well as for other life forms and life systems on this planet. Damien Rogers is Senior Lecturer in Politics and International Relations at Massey University, Auckland. A graduate of four universities, he holds a PhD in Political Science and International Relations from the Australian National University and a PhD in Law from the University of Waikato.